A Review on Diaphoresis Method in Traditional Chinese Medicine- An Alternative Treatment to Modern Diseases - Yap, Min Yi; Heng, Aik Teng; Wong, Ling Shing (INTI International University, 2018)
Sweat is the fluid that excretes out from the skin. In Traditional Chinese Medicine, treatment through sweating, or diaphoresis, refers to a treatment that expelling the exogenous pathogenic factors through sweating with the function of unblocking the superficial skin, regulating the nutrient-ying and defensive-wei phase, as well as dispersing the lung-qi. The treatment method has been applied for a long time in treating different diseases. In this review, the usage of diaphoresis in ancient and modern time is discussed.